Quasi-essentiality of RNase Y in Bacillus subtilis is caused by its critical role in the control of mRNA homeostasis - Benda, Martin; Woelfel, Simon; Faßhauer, Patrick; Gunka, Katrin; Klumpp, Stefan; Poehlein, Anja; Kálalová, Debora; Šanderová, Hana; Daniel, Rolf; Krásný, Libor; Stülke, Jörg (Nucleic acids research, 2021)
RNA turnover is essential in all domains of life. The endonuclease RNase Y (rny) is one of the key components involved in RNA metabolism of the model organism Bacillus subtilis. Essentiality of RNase Y has been a matter of discussion, since deletion of the rny gene is possible, but leads to severe phenotypic effects. In this work, we demonstrate that the rny mutant strain rapidly evolves suppressor mutations to at least partially alleviate these defects. All suppressor mutants had acquired a duplication of an about 60 kb long genomic region encompassing genes for all three core subunits of the RNA polymerase-α, β, β'. When the duplication of the RNA polymerase genes was prevented by relocation of the rpoA gene in the B. subtilis genome, all suppressor mutants carried distinct single point mutations in evolutionary conserved regions of genes coding either for the β or β' subunits of the RNA polymerase that were not tolerated by wild type bacteria. In vitro transcription assays with the mutated polymerase variants showed a severe decrease in transcription efficiency. Altogether, our results suggest a tight cooperation between RNase Y and the RNA polymerase to establish an optimal RNA homeostasis in B. subtilis cells.
Keywords: homeostáza; Bacillus subtilis; duplikace genu; transkriptom; DNA-Directed RNA Polymerases; RNA, Messenger; DNA řízené RNA-polymerasy; mutace; suprese genetická; Transcription, Genetic; Transcriptome; Homeostasis; molekulární evoluce; Evolution, Molecular; Gene Deletion; endoribonukleasy; Gene Duplication; genetická transkripce; Genes, Bacterial; Endoribonucleases; delece genu; Mutation; Suppression, Genetic; messenger RNA; bakteriální geny